Preoperative and intraoperative assessment of myometrial invasion and histologic grade in endometrial cancer: role of magnetic resonance imaging and frozen section. Issue 1 (1st January 2006) - SanjuÁN, A.; Cobo, T.; Pahisa, J.; EscaramÍS, G.; Ordi, J.; Ayuso, J. R.; Garcia, S.; HernÁNdez, S.; TornÉ, A.; RomÁN, S. Martínez; LejÁRcegui, J. A.; Vanrell, J. A.
Abstract : The objective of this study was to determine the value of myometrial invasion by magnetic resonance imaging (MRI), histologic typing and grading by endometrial biopsy, and the intraoperative evaluation of both parameters by frozen section in the evaluation of endometrial cancer. The preoperative and intraoperative records of 180 patients with endometrial cancer were used to compare the preoperative endometrial biopsy, the myometrial invasion by MRI, and the intraoperative frozen sections, with the final histopathologic findings. The preoperative endometrial biopsy gave us the tumor histologic type and grade. MRI gave us the depth of myometrial invasion. The evaluation of intraoperative frozen sections gave us the tumor histologic type, the tumor grade, and also the myometrial invasion. Patients were classified as low risk (grade 1 and 2, and myometrial invasion <50%) and high risk (grade 3 or myometrial invasion >50%). Standard statistical calculations were used. Evaluation of the tumor grade by preoperative biopsy has a sensitivity and a specificity of 75% and 95%, respectively. Evaluation of the tumor grade by intraoperative biopsy has a sensitivity and a specificity of 40% and 98%, respectively. Evaluation of the depth of myometrial invasion with MRI has a sensitivity and a specificity of 79% and 82%, respectively. Evaluation of the depth of myometrial invasion with intraoperative frozen sections has a sensitivity and a specificity of 74% and 95%, respectively. Evaluation of all four of the parameters together has a sensitivity and a specificity of 80% and 82%, respectively with a kappa of 0.621. In our opinion, the combination of preoperative biopsy and intraoperative frozen section is the best way to decide whether a lymphadenectomy is necessary with a low rate of understaging patients. MRI would have a fringe benefit in these patients.